2008
DOI: 10.1007/s10803-007-0505-y
|View full text |Cite
|
Sign up to set email alerts
|

Facial Feedback Mechanisms in Autistic Spectrum Disorders

Abstract: Facial feedback mechanisms of adolescents with Autistic Spectrum Disorders (ASD) were investigated utilizing three studies. Facial expressions, which became activated via automatic (Studies 1 and 2) or intentional (Study 2) mimicry, or via holding a pen between the teeth (Study 3), influenced corresponding emotions for controls, while individuals with ASD remained emotionally unaffected. Thus, individuals with ASD do not experience feedback from activated facial expressions as controls do. This facial feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 43 publications
(46 reference statements)
12
74
3
Order By: Relevance
“…This finding is somewhat different from the literature on facial expression mimicry which instead suggests similar effects of spontaneous and instructed mimicry [14,15]. One explanation for our finding is that the mechanisms of gesture-driven and facial emotional mimicry might differ.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is somewhat different from the literature on facial expression mimicry which instead suggests similar effects of spontaneous and instructed mimicry [14,15]. One explanation for our finding is that the mechanisms of gesture-driven and facial emotional mimicry might differ.…”
Section: Discussioncontrasting
confidence: 99%
“…We found a high level of spontaneous mimicry, as well as similar frequencies of mimicry behaviour in response to the SP's nonverbal emotional expressions, in both experimental and control groups. This novel finding affirms our lead question and suggests that non-verbal emotional expressions are mimicked by clinicians in simulated consultations either intentionally or unintentionally, consistent with the literature on the chameleon effect [7,9] and previous comparisons of instructed versus spontaneous mimicry in autistic spectrum participants [14,15]. However, our study reported much longer durations for instructed than spontaneous mimicry, probably reflecting the effort required to remember to mimic.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A compromise is to instruct participants or confederates to mimic in one experimental condition and refrain from mimicking in a control condition. Although this kind of instructed mimicry can reach similar levels to spontaneous mimicry (Stel, Dijk, & Olivier, 2009;Stel, van den Heuvel, & Smeets, 2008), this is not guaranteed. If untrained participants are instructed to mimic it is necessary to perform manipulation checks, such as asking the participant to report how well they followed the instruction (Maddux et al, 2008) or video recording their behaviour .…”
Section: Methodological Challenges and Future Directionsmentioning
confidence: 96%